A 12-week, Multicenter, Randomized, Double-blind, Placebo-controlled Clinical Trial Evaluating the Efficacy and Safety of DKB-131 in Knee Arthritis - Hee, Jeong Eom; Hyun, Il Jeong; Yu, Hwa Park; Sin, Jeong Park; Do, Hoon Kim (International Journal of Nutrition, 2024)
In this study, the efficacy and safety of DKB-131 (extract of Siraitiagrosvenorii) in adults of both genders presenting mild symptoms of knee arthritis were evaluated in comparison to a placebo. This clinical trial was randomized, double-blind, multicenter, and lasted for 12 weeks. A total of 120 participants with Visual Analogue Scale (VAS) scores of 30 mm or higher in the knee area and Kellgren & Lawrence Grade I or II knee arthritis on X-ray were enrolled, with 60 subjects randomized to receive DKB-131 and 60 subjects receiving placebo. Following 12 weeks of consumption, the change in K-WOMAC total score assessed in the per protocol (PP) set revealed a reduction of 21.86±15.98 points in participants who received DKB-131 (p<0.0001), whereas those in the placebo group exhibited a reduction of 14.92±16.66 points (p<0.0001). This demonstrated a statistically significant difference between the test groups (p=0.0389). Additionally, significant differences were observed between the DKB-131 and placebo groups in the changes in K-WOMAC pain (p=0.0157) and physical function (p=0.0447). For the secondary efficacy endpoint, the change in Visual Analogue Scale (VAS) scores, analyzed in the PP set after 12 weeks of consumption, the test group showed a reduction of 17.82±13.80 mm (p<0.0001), while the control group exhibited a reduction of 11.81±13.99 mm (p<0.0001), indicating a statistically significant difference between the test groups (p=0.0359). Safety evaluations including hematological tests, biochemical tests, and urinalysis revealed no clinically significant differences between the consumption groups. Additionally, vital signs (pulse, blood pressure) and anthropometric measurements (body weight) did not exhibit clinically significant differences between the consumption groups, confirming the safety of DKB-131. We propose that the consumption of DKB-131 is safe for humans and may contribute to joint health. Trial registration (CRIS.NIH.go.Kr): KCT0008527
Keywords: Dietary supplements; DKB-131; Siraitia grosvenorii; Luo Han Guo; Fruit extract; Arthritis; Clinical trial